Republic of Madagascar : Request for Disbursement Under the Rapid Credit Facility. (IMF Staff Country Reports; Country Report ;, 2014)
This paper focuses on Madagascar's Request for Disbursement Under the Rapid Credit Facility (RCF). The Malagasy authorities managed to avert a macroeconomic crisis during a difficult period of political transition and economic uncertainty since 2009. However, these disruptions have constrained growth and fiscal revenue, leading to a sharp compression of public investment and social outlays. The authorities are requesting a disbursement under the RCF. They also see the RCF as a stepping stone for a possible future arrangement addressing Madagascar's medium-term challenges and as a positive signal to development partners. The IMF staff supports the authorities' request for a disbursement under the RCF.